Plant-derived extracts and natural products with antiviral activity - Giovane de Jesus Gomes Ribeiro; Edmarcia Elisa de Souza; Giuseppe Palmisano; Edison Luiz Durigon; Edison Luiz Durigon; Eva Liebau; Carsten Wrenger; Carsten Wrenger (Frontiers in Virology)
In recent years, several viral epidemics and pandemics have emerged, leading to significant increases in both morbidity and mortality rates. This highlights the urgent need for the discovery of effective antiviral agents. A promising alternative approach to treating viral infections is the use of medicinal plants and their secondary metabolites. Plant-derived natural products have long been a valuable source for discovering novel therapeutic agents, owing to their chemical and structural diversity. This mini-review focuses on the antiviral activity of various enriched extracts and phytoconstituents isolated from medicinal plants, which have demonstrated efficacy against viral infections caused by the influenza virus, coronaviruses, arboviruses such as dengue, chikungunya, Zika, and Mayaro, as well as the human immunodeficiency virus (HIV).